Associations between salivary cytokines and oral health, age, and sex in healthy children - Charlotte Rinderknecht; Cornelia Filippi; Nicole Ritz; Nora Fritschi; Urs Simmen; Andreas Filippi; Tamara Diesch-Furlanetto (Scientific Reports, 2022)
Abstract Human saliva is a complex fluid containing proteins such as salivary cytokines, which can be used for diagnostic purposes, particularly among the pediatric population. This study aimed to assess the concentrations of salivary cytokines in healthy children and adolescents and determine their associations with age, sex, and oral and dental findings. Healthy children and adolescents aged 4–18 years were enrolled in this cross-sectional study. The concentrations of the following salivary cytokines were measured by Luminex technology: IFN-γ, IL-1α, IL-1β, IL-4, IL-5, IL-6, IL-8, IL-10, IL-13, IP-10, TNF-α, and VEGF-A. Additionally, oral and dental parameters were recorded using a standardized protocol. A total of 128 participants (mean age, 10.7 years; males, 50.8%) were enrolled. The levels of 1β, IL-6, IL-8, and IL-10 were significantly higher in those with gingivitis. Increased salivary flow rates were negatively correlated with IL-1α, IL-1β, IL-6, IL-8, IL-10, TNF-α, and VEGF-A concentrations. The findings of this study showed that the concentrations of most of the salivary cytokines were positively correlated with age and the presence of oral pathologies (such as gingivitis and caries) and negatively correlated with salivary flow rate.